Fiscal Supervision and the Soft Budget Constraint: Evidence from Germany - Désirée I. Christofzik; Sebastian G. Kessing (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study the effectiveness of local borrowing regulations in maintaining fiscal sustainability and the effect of supervision over municipal budgeting on local debt using a panel on municipalities in Germany's most populous state of North Rhine-Westphalia from 2003 to 2011. The identification strategy relies on a differences-in-differences approach and exploits the fact that a reform making it temporarily more likely to prevent financial supervision was implemented gradually across municipalities. We find that relaxing supervision temporarily leads to higher dept per capita.
Keywords: H72; H74; R10; 330